2019
DOI: 10.1001/jamaneurol.2019.2531
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes Associated With Clopidogrel-Aspirin Use in Minor Stroke or Transient Ischemic Attack

Abstract: IMPORTANCE Dual antiplatelet therapy with clopidogrel and aspirin is effective for secondary prevention after minor ischemic stroke or transient ischemic attack (TIA). Uncertainties remained about the optimal duration of dual antiplatelet therapy for minor stroke or TIA.OBJECTIVE To obtain precise estimates of efficacy and risk of dual antiplatelet therapy after minor ischemic stroke or TIA. DESIGN, SETTING, AND PARTICIPANTSThis analysis pooled individual patient-level data from 2 large-scale randomized clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(102 citation statements)
references
References 20 publications
2
99
0
1
Order By: Relevance
“…An important proportion of patients with ischaemic cerebrovascular disease (CVD) are not protected from recurrent vascular events with commonly prescribed 'non-monitored' antiplatelet therapy. Because the risk of recurrent events is highest early after a non-cardioembolic TIA/ischaemic stroke [1,2], early institution of an effective preventive antiplatelet regimen is very important [3].…”
Section: Introductionmentioning
confidence: 99%
“…An important proportion of patients with ischaemic cerebrovascular disease (CVD) are not protected from recurrent vascular events with commonly prescribed 'non-monitored' antiplatelet therapy. Because the risk of recurrent events is highest early after a non-cardioembolic TIA/ischaemic stroke [1,2], early institution of an effective preventive antiplatelet regimen is very important [3].…”
Section: Introductionmentioning
confidence: 99%
“…The primary outcome of interest will be recurrent ischemic stroke (Time-To-Event) up to 30 days. 30 days was chosen as the primary outcome because the majority of recurrent ischemic stroke events in this population occur within the first 21 days; data from trials investigating DAPT in this population have found that DAPT does not significantly reduce stroke risk during days 22–90 [ 18 ]. Time-To-Event (TTE) data will be presented as hazard ratios within intention-to-treat populations with 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Although most CRAO are assumed to have an arterial source of embolism, ipsilateral highgrade carotid artery stenosis is found in only a minority of these patients. In patients with CRAO and non-stenotic arteriosclerotic lesions of the supraaortic arteries, short time (21 days) dual antiplatelet therapy may be beneficial (analogous to data on patients with minor ischemic stroke and transient ischemic attack) [20]. Whether the antithrombotic treatment strategy should be influenced by the presence or absence of the spot sign (e.g., antiplatelet therapy vs. oral anticoagulation) is unclear.…”
Section: Plos Onementioning
confidence: 99%